The Effect of Satisfaction and Ease of Use on Loyalty and Its Impact on the Positive Word of Mouth of Brilink Users in Bandar Lampung - Saptarini, Atmi (FEB - Universitas Lampung, 2021)
The development of information technology, telecommunications and the internet has led to the emergence of various internet-based business applications. One of the banks that utilizes internet technology in serving its customers is Bank Rakyat Indonesia (BRI) with BRILink Mobile. The problem of this research is whether the variables of satisfaction and usability have an influence on loyalty and have an impact on positive word of mouth for brilink users. This study aims to determine the effect of satisfaction and usability on loyalty and its impact on positive word of mouth of brilink users. The sample of this study amounted to 150 and analyzed using multiple linear regression. The results of the study note that the role of the satisfaction variable as a usability mediating variable to form loyalty and has a relatively large positive impact on word of mouth. So that all hypotheses in this study can be accepted. The suggestion put forward is that BRI needs to improve the Brilink service connection so that failures when consumers transact can be avoided by working with telecommunications providers so that they get guaranteed reliable internet connections. As well as increasing the operator's ability can be done with training so that the speed and accuracy of the service can be increased. Keywords: satisfaction, usability, loyalty and positive word of mouth